Headache outcomes of a sleep behavioral intervention in breast cancer survivors: Secondary analysis of a randomized clinical trial. Issue 23 (6th August 2021) - Woldeamanuel, Yohannes W.; Blayney, Douglas W.; Jo, Booil; Fisher, Sophie E.; Benedict, Catherine; Oakley‐Girvan, Ingrid; Kesler, Shelli R.; Palesh, Oxana
Abstract : Background: Breast cancer survivors often have persisting headache. In a secondary analysis of the Brief Behavioral Therapy for Cancer‐Related Insomnia (BBT‐CI) clinical trial (ClinicalTrials.gov identifier NCT02165839), the authors examined the effects of BBT‐CI on headache outcomes in patients with breast cancer. Methods: Patients with breast cancer who were receiving chemotherapy were randomly assigned to receive either the BBT‐CI intervention or the Healthy EAting Education Learning for healthy sleep (HEAL) control intervention, and both were delivered over 6 weeks by trained staff. Headache outcomes and heart rate variability (HRV) were measured at baseline, 6 weeks, 6 months, and 12 months. Mixed‐effects models were used to examine longitudinal headache outcomes in the groups according to the intention to treat. Principal component analysis and agglomerative hierarchical clustering were conducted to reduce 16 variables for data‐driven phenotyping. Results: Patients in the BBT‐CI arm (n = 73) exhibited a significant reduction in headache burden over time ( P = .02; effect size [Cohen d] = 0.43), whereas the reduction was not significant among those in the HEAL arm (n = 66). The first principal component was positively loaded by headache, sleep, fatigue, and nausea/vomiting and was negatively loaded by cognitive, physical, and emotional functioning. Agglomerative hierarchical clustering revealed 3 natural clusters. Cluster I (n = 58) featured the highest burden of headache, insomnia, and nausea/vomiting; cluster II (n = 50) featured the lowest HRV despite a low burden of headache and insomnia; and cluster III (n = 31) showed an inverse relation between HRV and headache‐insomnia, signifying autonomic dysfunction. Conclusions: BBT‐CI is efficacious in reducing headache burden in breast cancer survivors. Patient phenotyping demonstrates a headache type featuring sleep disturbance, nausea/vomiting, and low physical functioning—revealing similarities to migraine. Lay Summary: Breast cancer survivors often have persisting headache symptoms. In patients with cancer, treatment of chronic headache disorders using daily medications may be challenging because of drug interactions with chemotherapy and other cancer therapies as well as patients' reluctance to add more drugs to their medicine list. Headache and sleep disorders are closely related to each other. This study demonstrates that a sleep behavioral therapy reduced headache burden in breast cancer survivors. In addition, the majority of headache sufferers had a headache type with similarities to migraine—featuring sleep disturbance, nausea/vomiting, and low physical functioning. Abstract : Breast cancer survivors often have persisting headache and insomnia burden. This study shows that a sleep behavioral therapy reduces headache burden in breast cancer survivors.